2014
DOI: 10.1002/ptr.5263
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Leishmanial, Anti-Inflammatory and Antimicrobial Activities of Phenolic Derivatives fromTibouchina paratropica

Abstract: A new phenolic derivative, 2,8-dihydroxy-7H-furo[2,3-f]chromen-7-one (1), together with isoquercitrin (2), was isolated from the aerial parts of Tibouchina paratropica. Compound structures were elucidated by spectroscopic methods. Both compounds show antimicrobial activity towards a panel of bacterial and fungal pathogens, and compound 1 displayed potent anti-parasitic activity against Leishmania donovani (IC50  = 0.809 µg/mL). In addition, an 85% reduction in the secretion of the pro-inflammatory cytokine IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The phytochemical data for C. hirta, C. capitellata and the other extracts were consistent with other studies (Gordon et al, 2011;Abdellaoui et al, 2014;Tracanna et al, 2015;Scalco and Munhoz, 2016). The absence of alkaloids in the extracts confirms this as a chemotaxonomic characteristic of the family Melastomataceae (Silva et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…The phytochemical data for C. hirta, C. capitellata and the other extracts were consistent with other studies (Gordon et al, 2011;Abdellaoui et al, 2014;Tracanna et al, 2015;Scalco and Munhoz, 2016). The absence of alkaloids in the extracts confirms this as a chemotaxonomic characteristic of the family Melastomataceae (Silva et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…However, other species within the genus have been reported to possess various biological activities such as wound healing and to treat cataract. [24] The isolated compounds 9 -11 from our study were found to be present in T. semidecandra L. leaves [12] which possess antioxidant and antityrosinase activities. [12] Furthermore, published data showed that compounds 7 and 8 possess antitumor [17] activities whereas compound 7 was believed to possess high antioxidant activity [17] and plays an important role in the prevention of malignant transformation and cancer development.…”
mentioning
confidence: 67%
“…Few examples of traditional uses are described in the literature for Tibouchina . Among them are anti-inflammatory, antioxidant [18], antinociceptive (relieving chronic pain) [19], antibacterial [20,21], antifungal [22,23], antiparasitic [20,24,25], and anticancer [26] activities of leaf extracts. Nonetheless, the chemical composition of Tibouchina largely remains elusive, with only eleven species being characterised phytochemically.…”
Section: Introductionmentioning
confidence: 99%